Cover Image, Volume 52, Issue 12. Issue 12 (15th June 2014) - Unknown
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> A series of highly fluorinated poly(phthalazinone ether)s with high molecular weights based on AB‐type monomers are synthesized by self‐condensation polymerizations, as presented by Xiuhua Li, Yan Gao, Qiang Long, and Allan S. Hay on page 1761 (DOI: 10.1002/pola.27199). The structure and properties of the fluorinated poly(phthalazinone ether)s are tuned by side groups of the AB‐type monomers. The polymers have very high glass transition temperatures (Tg) varying from 337 to 349 °C and show excellent solubility, thermal stability, mechanical properties, high water contact angles, and absorption edges below 340 nm.